Use of electronic medical records to conduct surveillance of malaria among Peace Corps volunteers. Issue 4 (7th October 2019) - Davlantes, Elizabeth; Henderson, Susan; Ferguson, Rennie W; Lewis, Lauren; Tan, Kathrine R
Abstract: Objective: The Peace Corps' disease surveillance for Peace Corps Volunteers (PCVs) was incorporated into an electronic medical records (EMR) system in 2015. We evaluated this EMR-based surveillance system, focusing particularly on malaria as it is deadly but preventable. Materials and Methods: In 2016, we administered a survey to Peace Corps Medical Officers (PCMOs), who manage PCVs' medical care, and semistructured phone interviews to headquarters staff. We assessed the structure of the surveillance system and its utility to stakeholders, evaluated surveillance case definitions for malaria, and compared clinical information in the EMR for malaria cases captured by surveillance during the first half of 2016. Results: Of 131 PCMOs, 77 (59%) completed the survey. Of 53 respondents in malaria-endemic nations, 98% believed most PCVs contact them about possible malaria. Of 134 cases with a malaria clinical diagnosis in the EMR between January and August 2016, 58 (43% sensitivity) were reported to the surveillance system by PCMOs. The remaining cases in the surveillance system were added during data cleaning, which is time-intensive. Among the 48 malaria cases identified by surveillance between January and June 2016, positive predictive value was 67%. Discussion: Areas for improvement include streamlining PCMO documentation, refining case definitions, and improving data quality. With such improvements, surveillance data can be used to inform epidemiological analysis, clinical care, health education, and policy. Conclusion: The EMR is an important tool for malaria surveillance among PCVs and, with the refinements mentioned, could serve as a framework for other multinational organizations to monitor their staff.